Globalization Education and Management Agendas - Cuadra-Montiel, Hector (IntechOpen, 2012)
The book Globalization - Education and Management Agendas takes the ambitious undertaking of presenting multidimensional approaches to those global issues. It consists of 13 chapters divided into three sections: Globalization and Education, Globalization and Management, Globalization and the Firm. Its authors embody a global research culture. One that is plural, growing and dynamic, as it is evidenced in their respective agendas and methodological approaches. The value of this book lies in its diversity, and its merit will be appreciated by a global community of scholars.